2013
DOI: 10.1007/s40368-013-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Streptococcus mutans and Lactobacillus fermentum and their association with caries and dietary habits in preschool Thai children

Abstract: Nested PCR gave a higher detection frequency than standard PCR but not significant (p ≤ 0.05). The prevalence of S. mutans was not different between the two groups, while the prevalence of L. fermentum was significantly associated with S-ECC (p ≤ 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The commonly‐found bacteria in infected root canals include Streptococcus spp., Enterococcus spp., and Staphylococcus spp . The most common etiological agent of endodontic infections, E. faecalis , is problematic because of its resistance to alkaline pH, all groups of cephalosporins and other antibiotics, and most of the substances used in endodontic treatment . Most bacteria are destroyed at pH 9.5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The commonly‐found bacteria in infected root canals include Streptococcus spp., Enterococcus spp., and Staphylococcus spp . The most common etiological agent of endodontic infections, E. faecalis , is problematic because of its resistance to alkaline pH, all groups of cephalosporins and other antibiotics, and most of the substances used in endodontic treatment . Most bacteria are destroyed at pH 9.5.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria can spread in the dentinal tubules and the periapical areas and colonize them, because the canal system morphology provides perfect conditions for microbial growth and biofilm formation . Different facultative anaerobic bacteria (such as Streptococcus mutans , Lactobacillus spp., Actinomyces spp., and many types of strictly‐anaerobic bacteria), in combination with the acids from enzymatic catabolism, have been reported as the major causes of dental decay, periapical lesions, and inflammation, which in turn can lead to periapical granulomas and pulp necrosis . In this process, oral hygiene and immune factors from the saliva, which interfere with the microbial invasion, play an important role .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A current concept of caries development is that the caries process is reversible and can shift back to the balance if it is detected early enough 6 . Streptococcus mutans is strongly associated with caries [7][8][9][10] . It was not only found in a high caries risk group but also in a low risk or cavities-free group 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Ecological plaque hypothesis suggested that an imbalance of microorganisms in oral biofilm results in a pathological condition such as dental caries and periodontitis 6 . Numerous studies have demonstrated a strong association between Streptococcus mutans and caries in regard to prevalence and transmission, as identical strains of S. mutans have been isolated from mothers and their children 4,[6][7][8][9][10] . Two important characteristics of S. mutans relates to plaque development: firstly, its ability to produce waterinsoluble polymers (glucan) which aid in the persistent adhesion and colonization on tooth surfaces by the action of a glucosyltransferases (GTFase) enzyme.…”
Section: Introductionmentioning
confidence: 99%